EFFECT OF PRESSURE IN ORGANIC WASTE BURNING PROCESS ON THE COMBUSTION RATE (Jurnal Bahan Alam Terbarukan, 2018)
The combustion process of organic waste has several drawback which produce flue gases containing pollutants SO2, HCl, tar and heavy metals (Cu, Hg, Fe, Zn, Pb, and Cr). The pollutants can be  removed  from the flue gas using a water scrubber. The process of absorption using the water scrubber  can cause a rise in pressure in the combustion chamber.This research aims to study the effect of combustion process pressure of organic waste on the combustion rate. The research was conducted by burning waste in the reactor at various flow rate of combustion air. The exhaust gases of combustion then flowed into ihe water scrubber that the height varied. The change in pressure and combustion rate of each variation of the air flow rate and the height of the water scrubber was measured. According to the results, it was obtained the correlation of combustion pressure to the  combustion rate was y = 0,844e-0,2X, where y = the combustion rate (kg/min) and x = combustion pressure (gauge, mm H2O). In addition, the increase in combustion pressure up to 21 mm of water, caused a reduction in combustion temperatures up to 50 ° C, while the combustion rate decreased to one-tenth from atmospheric combustion.